Gingipain R1 and Lipopolysaccharide From Porphyromonas gingivalis Have Major Effects on Blood Clot Morphology and Mechanics - Nunes, J. Massimo; Fillis, Tristan; Page, Martin J.; Venter, Chantelle; Lancry, Ophélie; Kell, Douglas B.; Windberger, Ursula; Pretorius, Etheresia (Frontiers in Immunology, 2020)
Background: Porphyromonas gingivalis and its inflammagens is associated with a number of systemic diseases, such as cardiovascular disease and type 2 diabetes (T2DM). The proteases, gingipains have also recently been identified in brains of Alzheimer’s disease patients and in blood of Parkinson’s disease patients. Bacterial inflammagens, including lipopolysaccharides (LPSs) and various proteases in circulation may drive systemic inflammation. Methods: Here, we investigate the effects of the bacterial products LPS from Escherichia coli and Porphyromonas gingivalis, and also the P. gingivalis gingipain (recombinant P. gingivalis gingipain R1 (RgpA)), on clot architecture and clot formation in whole blood and plasma from healthy individuals, as well as in purified fibrinogen models. Structural analysis of clots was performed using confocal, scanning electron microscopy and AFM-Raman. We use thromboelastography (TEG) and rheometry to compare the static and dynamic mechanical properties of clots. Results: We found that these inflammagens may interact with fibrin(ogen) and this interaction causes anomalous blood clotting. Conclusions: These techniques, in combination provide insight into the effects of these bacterial products on cardiovascular health, and particularly clot structure and mechanics.